Absolute quantification of viable Vibrio cholerae in seawater samples using multiplex droplet digital PCR combined with propidium monoazide - Yang, Jinsong; Xu, Haibin; Ke, Zili; Kan, Naipeng; Zheng, Enhui; Qiu, Yufeng; Huang, Mengying (Frontiers in Microbiology, 2023)
Toxigenic Vibrio cholerae (V. cholerae) serogroup O1 and O139 are the pathogens responsible for the global cholerae epidemic. V. cholerae can settle in the water and spread via the fecal-oral route. Rapid and accurate monitoring of live V. cholerae in environmental water has become an important strategy to prevent and control cholera transmission. Conventional plate counting is widely used to detect viable bacteria but requires time and effort. This study aims to develop a new assay that combines triplex droplet digital PCR (ddPCR) with propidium monoazide (PMA) treatment for quantitatively detecting live V. cholerae O1/O139 and cholera enterotoxin. Specific primers and probes were designed according to the conserved regions of gene rfb O1, rfb O139, and ctxA. The amplification procedures and PMA treatment conditions were optimized. The specificity, sensitivity, and ability of PMA-ddPCR to detect viable bacteria-derived DNA were evaluated in spiked seawater samples. The results revealed that the optimal primer concentrations of rfb O1, rfb O139, and ctxA were 1 μM, while the concentrations of the three probes were 0.25, 0.25, and 0.4 μM, respectively. The best annealing temperature was 58℃ to obtain the most accurate results. The optimal strategy for distinguishing dead and live bacteria from PMA treatment was incubation at the concentration of 20 μM for 15min, followed by exposure to a 650-w halogen lamp for 20 min. In pure culture solutions, LODs of V. cholerae O1 and O139, and ctxA were 127.91, 120.23 CFU/mL, and 1.5 copies/μL in PMA-triplex ddPCR, respectively, while the LODs of the three targets were 150.66, 147.57 CFU/mL, and 2 copies/μL in seawater samples. The PMA-ddPCR sensitivity was at least 10 times higher than that of PMA-qPCR. When detecting spiked seawater samples with live bacterial concentrations of 1.53×102 and 1.53×105 CFU/mL, the assay presented a higher sensitivity (100%, 16/16) than qPCR (50.00%, 8/16) and a perfect specificity (100%, 9/9). These results indicate that the developed PMA-triplex ddPCR is superior to the qPCR regarding sensitivity and specificity and can be used to rapidly detect viable toxigenic V. cholerae O1 and O139 in suspicious seawater samples.